2007
DOI: 10.1210/me.2007-0169
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 Coordinately Regulates Expression of Genes Linked to Glucose Metabolism in Skeletal Muscle

Abstract: Innervation is important for normal metabolism in skeletal muscle, including insulin-sensitive glucose uptake. However, the transcription factors that transduce signals from the neuromuscular junction to the nucleus and affect changes in metabolic gene expression are not well defined. We demonstrate here that the orphan nuclear receptor Nur77 is a regulator of gene expression linked to glucose utilization in muscle. In vivo, Nur77 is preferentially expressed in glycolytic compared with oxidative muscle and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
160
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 49 publications
17
160
1
3
Order By: Relevance
“…Nr4a family members were shown to exert transcriptional activity in a ligand-independent manner (6), and they have been implicated in the regulation of glucose metabolism, apoptosis, and inflammation, as well as the differentiation of monocytes and T cells (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Nr4a family members were shown to exert transcriptional activity in a ligand-independent manner (6), and they have been implicated in the regulation of glucose metabolism, apoptosis, and inflammation, as well as the differentiation of monocytes and T cells (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…18 Both LXRa and LXRb increase target gene transcription by binding to DNA sequence motifs composed of two hexameric nucleotide direct repeats separated by four bases (DR-4). 19 Although in the earlier study, LXRa and NOR-1 were separately shown to participate in regulating genes involved in metabolic fuel usage, [7][8][9][10]16,20 our current studies in adipocytes identify a direct involvement of LXRa to regulate NOR-1 gene transcription through a DR-4 element in the NOR-1 promoter.…”
Section: Introductionmentioning
confidence: 52%
“…NR4A receptors were shown to contribute to the cAMP-dependent transcription of glucose-6-phosphatase in the liver, a key step in hepatic gluconeogenesis, 10 as well as to the regulation of genes involved in glucose and oxidative metabolism in skeletal muscle. 8,26 In adipose tissue, NR4As have been linked to the recruitment of GLUT4 receptors to the plasma membrane, resulting in improved insulin sensitivity, 7 and in brown adipocytes, NOR-1 contributes to the cAMP-dependent transcription of the Ucp1 gene, the induction of which is necessary for sustained adaptive thermogenesis. 9 Our finding of another transcriptional regulatory pathway to regulate NR4As, and the NOR-1 gene in particular in response to LXR, underscores the fact that we still do not know the full extent to which there is cross-talk between the nuclear receptor families to modulate each other's expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that NR4A1 overexpression inhibited adipogenesis in 3T3‐L1 pre‐adipocytes. In vivo, it has been reported that NR4A1 had the effects on glucose and lipid metabolism in liver 31, 32 and muscles 30, 33. Studies have shown that NR4A1 knockout mice fed with high‐fat diet were more likely to develop obesity compared to WT mice 23.…”
Section: Discussionmentioning
confidence: 99%